Fungsi Pemerintah Desa Dalam Pembangunan Desa di Desa Weain dan Desa Webetun, Kecamatan Rinhat, Kabupaten Malakaa - Hoar, Sisilia Derlince; Yohanes, Saryono; Tupen, Rafael (Artemis Law Journal, 2024)
The symptoms seen by the author one of the main factors that make the community complain about the duties and functions of the village government is the uneven development carried out by the village government because the village government focuses more on carrying out development for families than equitable distribution of development for local village communities. The problem formulation in this research is: (1) What is the function of the Village Government in village development in Weain Village and Webetun Village, Rinhat District, Malaka Regency? (2) What are the inhibiting factors in implementing village development functions in Weain Village and Webetun Village, Rinhat District, Malaka Regency? The objectives of this research are: (1) to find out and describe the duties and functions of the Village development in Weain Village and Webetun Village, Rinhat District, Malaka Regency, (2) to find out and describe the inhibiting aspects in implementing development in Weain Village and Webetun Village, Rinhat District, Malaka Regency.This research uses empirical legal research methods and normative juridical legal research methods. The results of this research show: (1) The function of the village government in village development in Weain Village and Webetun Village, Rinhat District, Malaka Regency, namely: (a) Village development planning stage, (b) Implementation of village development, (c) Accountability stage, (2) Factors that become obstacles in the implementation of village development in Weain Village and Webetun Village, namely: (a) Low human resources, low understanding and level of education so that many opportunities are not touched.